(untitled) (International journal of artificial intelligence, 2024)
Cutaneous leishmaniasis, including a large class of Leishmanias, is widespread in Uzbekistan. Leishmanias are parasites belonging to the class of flagellates and differ from representatives of other classes in that they have one flagella throughout their body. Currently, skin leishmaniasis frequently disturbs the population in the regions of Uzbekistan, especially in the city of Termiz of the Surkhandarya region. Skin leishmania parasite does not cause a very dangerous disease to the human body, but it has the characteristic of forming a bad wound on the skin and leaving a strong scar.